Squanio a warrior's tale : a novel - Fontes, Ron.; Korman, Justine; Craviotto, Darlene; Dolman, Bob.; Walt Disney Pictures (Mahwah, N.J. : Troll Associates, 1994)
Squanto is kidnapped to England and put on display, until he escapes and is aided in his return to America by friendly monks.
Keywords: Squanto -- Juvenile fiction; Squanto -- Fiction -- Juvenile fiction; Wampanoag Indians -- Juvenile fiction; Indians of North America -- Juvenile fiction; Pilgrims (New Plymouth Colony) -- Fiction